2022
DOI: 10.5267/j.ccl.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation intervals and foliar spray of zinc and silicon treatments on maize growth and yield components of maize

Abstract: Field experiments were carried out for two consecutive seasons at the Experimental Shandaweel Agricultural Research Station, Sohag Governorate, Upper Egypt, during the growing seasons of 2013 and 2014, to study the Effect of Irrigation intervals and foliar spray of zinc and silicon treatments on Maize growth and yield components of maize. Results indicated that, scheduling at every 10 days produced the highest plant height, Flag Leaf area (cm²), Cob length (cm), Weight of 100-grains (g), Biological yield (T/fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Furthermore, the vegetative growth measurements (plant height, diameter, and number of green leaves per plant), yield, and its component attributes (average ear length, ear weight, number of grains per ear, weight of 1000 grains, and grain yield) in maize plants irrigated every 10 days and when fertilised with a 114 kg K 2 O•ha -1 potassium fertiliser were significantly higher than in plants irrigated every 7 days without fertiliser, as shown in Tables S2 and S3. These findings are in line with Abdelgalil et al (2022). They mentioned that irrigation at every 10 days produced the highest plant height, cob length, weight of 100 grains and grain yield as compared to the irrigation every 15 and 20 days.…”
Section: � Number Of Grains Per Earsupporting
confidence: 82%
“…Furthermore, the vegetative growth measurements (plant height, diameter, and number of green leaves per plant), yield, and its component attributes (average ear length, ear weight, number of grains per ear, weight of 1000 grains, and grain yield) in maize plants irrigated every 10 days and when fertilised with a 114 kg K 2 O•ha -1 potassium fertiliser were significantly higher than in plants irrigated every 7 days without fertiliser, as shown in Tables S2 and S3. These findings are in line with Abdelgalil et al (2022). They mentioned that irrigation at every 10 days produced the highest plant height, cob length, weight of 100 grains and grain yield as compared to the irrigation every 15 and 20 days.…”
Section: � Number Of Grains Per Earsupporting
confidence: 82%
“…Moreover, the drought stress conditions resulted in diminished vegetative and reproductive growth, as evidenced by decreased plant height, dry and fresh weights, ears per plant, ear weight, and grain yield. Abdelgalil et al, (2022) conducted a study to explore the impact of varying irrigation intervals on the growth and yield of maize. The outcomes revealed that the most favorable outcomes in terms of plant height, cob length, biological yield, and grain yield were observed with irrigation occurring every 10 days.…”
Section: Effect Of Water Deficit On Maize Performancementioning
confidence: 99%